Gestational Sympathetic Stress Programs the Fertility of Offspring: A Rat Multi-Generation Study - Barra-Pezo, R (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The exposure to sympathetic stress during the entire period of gestation (4 °C/3 h/day) strongly affects the postnatal reproductive performance of the first generation of female offspring and their fertility capacity. The aim of this work was to determine whether this exposure to sympathetic stress affects the reproductive capacity of the next three generations of female offspring as adults. Adult female Sprague–Dawley rats were mated with males of proven fertility. We studied the reproductive capacity of the second, third, and fourth generations of female offspring (the percentage of pregnancy and the number and weight of female offspring). The estrus cycle activity of the progenies was studied, and a morphological analysis of the ovaries was carried out to study the follicular population. The second generation had a lower number of pups per litter and a 20% decrease in fertile capacity. The estrus cycle activity of the third generation decreased even more, and they had a 50% decrease in their fertile capacity, and their ovaries presented polycystic morphology. The fourth generation however, recovered their reproductive capacity but not the amount of newborns pups. Most probably, the chronic intrauterine exposure to the sympathetic stress programs the female gonads to be stressed in a stressful environment; since the fourth generation was the first born with no direct exposure to stress during development, it opens studies on intrauterine factors affecting early follicular development. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.